THE GLOBAL ECONOMIC CONSEQUENCES OF THE RUSSIAUKRAINE WAR: IMPLICATIONS FOR ENERGY, FOOD SECURITY, POST-COVID RECOVERY, AND REGIONAL ECONOMIC STABILITY - Ghulam Mustafa Noorani; Ms. Tooba Aslam Khan; Hameed Ullah Khan (Policy Research Journal, 2024)
Ukraine's sovereignty, alongside its geopolitically important region between Europe and Russia, has seen the emergence of a Russia-Ukraine conflict which has resulted in negative prospects for global economies. This study outlines the broader impacts of this war, such as its effects on energy, food security and post-COVID growth as well as certain regional economic weaknesses. Tensions increased after the Russian annexation of Crimea in 2014 which led to active warfare in Eastern Ukraine, sparking further hostile economic activity across the globe. The war has also brought forth the deficiencies of established global supply chains and pointed out the vulnerability of several nations with their energy needs sourced out in Russia and agricultural goods from Ukraine. Global economic challenges have therefore become greater for developing economies. There is need for pro-active strategies at the international level to counter such threats, which may involve energy diversification, food sourcing strategies, and debt write offs as well as collaboration-oriented initiatives. If these challenges can be overcome, enhanced economic growth and stability shall be achievable in the continued presence of varying degrees of uncertainty.